The development of Munshi Abdullah's framework of modernity in malay literature: A critical observation - Hamdan, Rahimah (Dewan Bahasa dan Pustaka, 2023)
The West introduced modernity in literature to relevantize their contribution to scholarship in the Malay Archipelago. This led to the acknowledgement of Munshi Abdullah as a key reformer. Despite various scholarly discussions concerning the modernity of Munshi Abdullah’s writing, there has been no systematic idea in relation to the framework of the modernity of his writings. Thus, this study aims to organise scholars’ views on Munshi Abdullah’s modernity in Malay literature from the colonial era to now and create a framework for it. This study employs a qualitative method in the form of grounded theory. It is a method of deriving theories directly from gathered data that is systematically analysed using comparative analysis. The findings outline the framework of modernity in literature by Munshi Abdullah based on two concepts; realism and individualism. Realism emphasises logical thinking and the rejection of superstitions, while individualism highlights on individual viewpoints and the rejection of institutional authority. Through the construction of this framework, studies concerning modernity in traditional and modern literary works can be carried out systematically. Lastly, this study may broaden the audience’s understanding of the modernity of Munshi Abdullah’s writings, which, up until now, has not been supported by a clear framework.